1997
DOI: 10.1111/j.1745-493x.1997.tb00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Green Purchasing Strategies: Trends and Implications

Abstract: IN BRIEF Over the last two decades, growing concerns about ecosystem quality have led to a renewed interest in environmentalism. Purchasing professionals should also be concerned and need to rethink purchasing strategies which have traditionally neglected environmental impacts. To help foster environmentally concerned purchasing strategies, this article presents the findings of an empirical survey of NAPM members in firms with a high level of awareness and frequent applications of “green” purchasing. Environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
281
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(295 citation statements)
references
References 4 publications
(2 reference statements)
10
281
1
3
Order By: Relevance
“…Customer awareness on the importance of environmental conservation had increased over the last decades (Min & Galle 1997). Customer pressures are instilled within the firm's supply chain when green practices are implemented to meet environmental and social needs (Rao 2007).…”
Section: Customer Pressuresmentioning
confidence: 99%
“…Customer awareness on the importance of environmental conservation had increased over the last decades (Min & Galle 1997). Customer pressures are instilled within the firm's supply chain when green practices are implemented to meet environmental and social needs (Rao 2007).…”
Section: Customer Pressuresmentioning
confidence: 99%
“…However, there may be a perception that costs for environmental management training, and the purchase of software programmes and tools, cannot be outweighed by the benefits [97][98][99][100]. Consequently, investments need to have significant short-term financial benefits for them to be considered [101].…”
Section: Resource Availabilitymentioning
confidence: 99%
“…Min and Galle [26] indicated that green procurement affect environmental practices and create positive business conducts [27].…”
Section: Business Performancementioning
confidence: 99%
“…The research of Ellaram and Pearson showed that green procurement reduces environmental impacts, which correspond with Min and Galle [26][27][28].…”
Section: Environmental Performancementioning
confidence: 99%